The Nature of Family Life among Marginalized People Living with HIV/AIDS in the Canadian Prairies. Issue 3 (July 2014) - Harvey, Carol D. H.; Migliardi, Paula; Mignone, Javier
This article reports on family life for a group of individuals living with HIV/AIDS from Winnipeg, Manitoba, and Regina, Saskatchewan, Canada. Participants took photos of people and things that provided support to deal with their disease; they then described the photos, and their narratives were used as data points for this analysis. Eight themes were revealed, and we report on one, family life, which has three subthemes: (a) family separation, shown across the life cycle, from adoption of respondents or of their children; from illness or death of parents, siblings, or offspring; and from physical separation; (b) family support (or lack thereof); and (c) family violence, either physical or psychological, that was frequent and formed the context for interaction. These subthemes are discussed and implications for practice and research are presented.